Antibodies against multiple merozoite surface antigens of the human malaria parasite Plasmodium falciparum inhibit parasite maturation and red blood cell invasion - Wöhlbier, Ute; Epp, Christian; Hackett, Fiona; Blackman, Michael J.; Bujard, Hermann (Malaria journal, 2010)
Plasmodium falciparum merozoites expose at their surface a large protein complex, which is composed of fragments of merozoite surface protein 1 (MSP-1; called MSP-183, MSP-130, MSP-138, and MSP-142) plus associated processing products of MSP-6 and MSP-7. During erythrocyte invasion this complex, as well as an integral membrane protein called apical membrane antigen-1 (AMA-1), is shed from the parasite surface following specific proteolysis. Components of the MSP-1/6/7 complex and AMA-1 are presently under development as malaria vaccines.
Gesehen am 15.03.2024